Techno-economic analysis of producing liquid fuels from biomass via anaerobic digestion and thermochemical conversion. (November 2019) - Naqi, Ahmad; Kuhn, John N.; Joseph, Babu
Abstract: This paper discusses a preliminary design and a techno-economic analysis of a process that produces liquid hydrocarbon fuels from biomass through a combined biochemical and thermochemical process. The biochemical component involves anaerobic digestion (AD) of the biomass's biodegradable portion to produce biogas. Biogas is purified by removing contaminants and upgraded to liquid hydrocarbon fuel in a biogas to liquid facility (BGTL) via thermochemical conversion route. The BGTL process involves two major steps: tri-reforming to produce syngas (a mixture of CO and H2 ), and, Fischer-Tropsch Synthesis (FTS) to convert the syngas to a spectrum of hydrocarbons (synthetic crude). Separation and upgrading of the produced hydrocarbon mixture allows production of transportation fuels such as gasoline, jet fuel, and diesel. In order to evaluate the economics of the combined process a detailed process modelling was carried out using Aspen Plus® software. Bench-scale experimental results served as the basis of modelling the BGTL section of the plant, while the AD portion of the plant is based on empirical models selected from the literature validated by comparison with experimental results. Recent bench scale tests in our lab were used to determine processing parameters (yield, temperature, and pressure) for the reforming and FTS conversion. A plant capable of processing 90, 000 tonne year −1 of wet biomass feed was designed and analyzed using the model. Results of the economic analysis estimate that a breakeven cost of diesel of 1.30 L -1 is achievable without the consideration of charging tipping fees to accept the biomass feedstock. Sensitivity study shows that the economics are significantly affected by the fixed capital investment (FCI) and less so by the operating expenses and interest rate. In addition, tipping fees and biomass feedstock cost have a substantial effect on the breakeven price of diesel. Graphical abstract: Image 1 Highlights: Design/techno-economics of biomass to liquids with bio- and thermo-chemical steps. Plant capable of processing 90, 000 metric tons per year of wet waste biomass feed. Estimation of 175 L diesel per dry metric ton of biomass. Breakeven cost of diesel estimated as 1.02 per liter when no feedstock cost. Fixed capital investment, tipping fees, and feedstock cost have substantial impact.